Importance of technology in environmental protection: cloud computing as a key tooL - Olvera Vera, Luis Amilcar; Salcedo Aparicio, Denisse Maricela; Rosero Lozano, Jenny Maritza (Scripta Mundi, 2022)
Companies in general know about the social responsibility involved in taking care for the environment, with this it should be noted that technology plays a key role in protecting the environment and cloud services have become an important tool to reduce the environmental impact of the technology industry, but few institutions are aware of the environmental impact they generate, and with this they contribute to deforestation, plastic waste and pollution, for this reason it is essential to think of alternatives that reduce energy consumption, giving opportunity for companies to use remote data centers that store and process data instead of maintaining physical servers and equipment; respect for the environment is also promoted. This study analyzes the importance of technology in environmental protection, focusing on: cloud computing as a key tool, it is descriptive, with a qualitative approach based on a bibliographic review, using cloud computing and environmental protection as research variables, linking technological advances in favor of the caring for the environment. Thus, cloud computing seems to play a fundamental role in our lives, on the one hand, in order to provide citizens with increasingly accessible and developed services, and on the other hand, to contribute to efficiency and competitiveness, which provides a practice way and effective method. Ways to save money, time and work in day-to-day management. Information and Communication Technologies (ICTs) are an excellent option when thinking about reducing environmental impact.